THE PARADIGM SHIFT OF COMIC AS STORYTELLING MEDIA - Sutanto, Shienny Megawati; Wardaya, Marina (Universitas Ciputra, 2020)
Comics are media stories that are not specific to a particular group of readers. But in reality, comics are often regarded as mere children's reading. This raises a negative paradigm for comics, and comics are considered as reading that degrades children's morale. This article will describe the history, definition, and function of comics as storytelling media, and how the negative paradigm affects the comic industry in Indonesia. As a medium, the comic is a means to convey messages similar to television, radio, newspapers, and magazines. And similar to other media, comics can be used to convey various kinds of information, not merely intended for entertainment only. Various kinds of messages, ranging from advertorials, political propaganda, public services, even education, can all be conveyed using comic media. However, most people still believe the false paradigm that that comic is only for children. This is a misunderstanding and is not true. Since the beginning, the Indonesian comic industry has always tried to grow and counter the negative paradigm. In order to revitalize comics as one Indonesian creative industry subsector, a paradigm shift on how the society values and appreciates comics not just as child reading material needs to happen. Keyword: comic, media, story, paradigm shift, creative industry.